Analysis on Hot Carrier Injection of 0.15 μm Short-Channel AlGaN/GaN HEMTs Using Electroluminescence Spectroscopy - Junwoo Jung; Jong-Min Lee; Byoung-Gue Min; Dong Min Kang; Inho Kang; Hyungtak Kim (Journal of Electromagnetic Engineering and Science)
In this work, we analyzed the effects of hot carrier injection in short-channel AlGaN/GaN high electron mobility transistors by identifying hot carrier stress conditions using electroluminescence (EL) spectroscopy. After applying hot carrier stress, degradation of the device parameters was observed. This degradation worsened under conditions of peak EL signal intensity (VG = −3 V, VD = 40 V), which accelerated the generation of hot carriers. However, when the devices were subjected to on-state stress while maintaining the same power consumption as in hot carrier stress conditions, almost no degradation was detected. This suggests that the primary cause of degradation under hot carrier stress conditions is the continuous generation of hot carriers, which is accelerated by a high electric field. This further demonstrates the feasibility of using EL spectroscopy to identify conditions for the accelerated degradation of device parameters caused by hot carriers.